"Utter Failure" or Unity out of Diversity? Debating and Evaluating Policies of Multiculturalism1. (September 2014) - Bloemraad, Irene; Wright, Matthew
Abstract : Across immigrant‐receiving democracies, "multiculturalism" has come under assault by political decision‐makers and commentators. The academic debate, while less fiery, is also heated. We start by outlining the multiple meanings of "multiculturalism": a term for demographic diversity; a political philosophy of equality or justice; a set of policies to recognize and accommodate ethno‐racial and religious diversity; or a public discourse recognizing and valorizing pluralism. We then review the existing empirical literature and offer some new statistical analyses to assess what we know about the harm or benefits of multicultural policies, focusing on sociopolitical outcomes. We conclude that multicultural policies appear to have some modest positive effects on sociopolitical integration for first‐generation immigrants and likely little direct effect, positive or negative, on those in the second generation. On the question of majority backlash, the limited scholarship is mixed; we speculate that multiculturalism works best in places where both minorities and majority residents see it as part of a common national project. We end by considering the conditions under which this happens and whether there are distinctions between "Anglo‐settler" and other countries.